Mandibelrudimente der Anopluren und ihre stammesgeschichtliche Bedeutung. - Kéler, Stefan von (Contributions to Entomology = Beiträge zur Entomologie, 1961)
The Author describes mandibular vestiges of some anopluran genera and states that the oral (peristomal) margin of the head capsule of these insects, which has hitherto been neglected, possesses fundamental value for the interpretation of the head capsule and of their musculature. The correctness of the present day interpretation of the head capsule and their musculature in Anoplura is stated to be questionable.